Analisis Struktur Gedung Perpustakaan terhadap Gaya Gempa di Kota Sungai Penuh - Anisa Nafail Adilah; Suhendra Suhendra; Wari Dony; Ria Zulfiati (Jurnal Talenta Sipil, 2026)
The Kerinci area and the city of Sungai TFull are one of the areas prone to earthquakes because they are located close to the confluence of the active lemma of Sumatra and are on the path of the world's active fires. Of course, it is a consideration in the development of analysis in the planning of earthquake-resistant buildings. This study will analyze a 4-storey building that functions as a Library Building using the Spectrum Response Dynamics method. The purpose of this study is to analyze the structure of earthquake-resistant buildings in accordance with SNI 1726:2019. This analysis uses the ETABS program supplements. The results of the study stated that the structure had met the criteria for mass participation and basic shear force in accordance with SNI 1726:2019, but did not meet the eligibility requirements as an earthquake-resistant building due to horizontal irregularities and vertical irregularities as well as the exceedance of the intersection boundary between floors at several levels. The effect of P-Delta is negligible because the boundary coefficient of each floor is less than 0.10